Costa y serranía: construcciones socio-culturales de territorios para el ocio en el sudeste de la provincia de Buenos (Argentina), primera mitad del siglo XX - Gisela Paola Kaczan; Lorena Marina Sánchez (Études Caribéennes)
The southeast zone of the province of Buenos Aires (Argentina), it is glimpsed as fertile territory for the cultural studies due to its historical, social and heritage density, in a frame of dissimilar geographical conditions. Two intermediate cities, Mar del Plata and Tandil, have been outlined for their processes of sociocultural constructions associated with leisure and tourism. The proposed study includes the first half of the XXth century to recognize the transformations happened in the habitat and the living, observing the social practices and the renewed relations between body and space that will give place to different proposals in relation with the coastal or highland demurrage. For this, it will be emphisized in the reading of the illustrated magazine Caras y Caretas, especially, the images of notes and advertising notices.